2021
DOI: 10.3390/foods10020314
|View full text |Cite
|
Sign up to set email alerts
|

Peroxidized Linoleic Acid, 13-HPODE, Alters Gene Expression Profile in Intestinal Epithelial Cells

Abstract: Lipid peroxides (LOOHs) abound in processed food and have been implicated in the pathology of diverse diseases including gut, cardiovascular, and cancer diseases. Recently, RNA Sequencing (RNA-seq) has been widely used to profile gene expression. To characterize gene expression and pathway dysregulation upon exposure to peroxidized linoleic acid, we incubated intestinal epithelial cells (Caco-2) with 100 µM of 13-hydroperoxyoctadecadienoic acid (13-HPODE) or linoleic acid (LA) for 24 h. Total RNA was extracted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 90 publications
2
2
0
Order By: Relevance
“…This reaction may be triggered by the intake of TGOOH. Previously, dietary lipid hydroperoxides have been reported to cause oxidative stress that induces pro-inflammatory changes in the gastrointestinal tract [ 32 , 33 , 38 , 39 ]. Separately, other studies reported that an inflamed intestinal mucosa is highly infiltrated with neutrophils ( e.g., in ulcerative colitis patients [ 40 , 41 ]), which generate 1 O 2 via the myeloperoxidase system of activated phagocytosis as the initial defense mechanism against tissue damage [ [42] , [43] , [44] ].…”
Section: Resultsmentioning
confidence: 99%
“…This reaction may be triggered by the intake of TGOOH. Previously, dietary lipid hydroperoxides have been reported to cause oxidative stress that induces pro-inflammatory changes in the gastrointestinal tract [ 32 , 33 , 38 , 39 ]. Separately, other studies reported that an inflamed intestinal mucosa is highly infiltrated with neutrophils ( e.g., in ulcerative colitis patients [ 40 , 41 ]), which generate 1 O 2 via the myeloperoxidase system of activated phagocytosis as the initial defense mechanism against tissue damage [ [42] , [43] , [44] ].…”
Section: Resultsmentioning
confidence: 99%
“…Although the mechanism of 13-PHODE in the pathogenesis of diabetic retinopathy has not been clarified so far, 13-PHODE has been found to induce inflammatory responses in animal models, which could significantly induce pro-inflammatory gene expression of TNF-α and MCP-1 in vitro , most notably in differentiated intestinal epithelial cells ( Keewan et al, 2020 ). The possible involvement of 13-PHODE in mitochondrial dysfunction-related disorders has also been reported ( Faizo et al, 2021 ). Further studies are needed to confirm our findings.…”
Section: Discussionmentioning
confidence: 98%
“…Although the mechanism of 13-PHODE in the pathogenesis of diabetic retinopathy has not been clarified so far, 13-PHODE has been found to induce inflammatory responses in animal models, which could significantly induce pro-inflammatory gene expression of TNF-α and MCP-1 in vitro, most notably in differentiated intestinal epithelial cells (Keewan et al, 2020). The possible involvement of 13-PHODE in mitochondrial dysfunctionrelated disorders has also been reported (Faizo et al, 2021). Further studies are needed to confirm our findings.…”
Section: Discussionsupporting
confidence: 62%